Higher education students' achievement emotions and their antecedents in e-learning amid COVID-19 pandemic: A multi-country survey. (August 2022) - Raccanello, Daniela; Balbontín-Alvarado, Roxana; Bezerra, Denilson da Silva; Burro, Roberto; Cheraghi, Maria; Dobrowolska, Beata; Fagbamigbe, Adeniyi Francis; Faris, MoezAlIslam Ezzat; França, Thais; González-Fernández, Belinka; Hall, Rob; Inasius, Fany; et al.
Abstract: The outbreak of the COVID-19 pandemic has had a wide range of negative consequences for higher education students. We explored the generalizability of the control-value theory of achievement emotions for e-learning, focusing on their antecedents. We involved 17019 higher education students from 13 countries, who completed an online survey during the first wave of the pandemic. A structural equation model revealed that proximal antecedents (e-learning self-efficacy, computer self-efficacy) mediated the relation between environmental antecedents (cognitive and motivational quality of the task) and positive and negative achievement emotions, with some exceptions. The model was invariant across country, area of study, and gender. The rates of achievement emotions varied according to these same factors. Beyond their theoretical relevance, these findings could be the basis for policy recommendations to support stakeholders in coping with the challenges of e-learning and the current and future sequelae of the pandemic. Highlights: We conducted a multi-country online survey on higher education students' emotions. We assessed achievement emotions related to e-learning during the pandemic. Environmental antecedents predicted achievement emotions through self-efficacy. The model was invariant across genders, areas of study, and countries. Policies should focus on supporting students' achievement emotions and correlates.